Akurasi Nilai Tinggi Matahari Antara Perhitungan Daftar Ilmu Pelayaran (DIP) Dan Sight Reduction Table (SRT) - I Made Wahyu S.P; Slamet Riyadi; Dwi Antoro; Hilda Emeraldo A.A (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2021)
Positioning with celestial bodies (celestial navigation) is the art of determining on the surface of the earth based on measurements of celestial bodies which have guided sailors for hundreds of years. Astronomical positioning methods or celestial body navigation are becoming increasingly obsolete and rarely used. The fact is that today, along with technological advances, seafarers prefer to use electronic navigation tools such as the Global Positioning System (GPS). The the International Convention on Standard of Training, Certification and Watchkeeping for Seafarers (STCW) amended 2011, requires all officers on board responsible for navigation to be able to determine the height of celestial bodies, the Line of Position (LOP) and the position of the ship. In general, there are 2 methods of determining the navigation position of celestial bodies, namely by calculating the Sight Reduction Table. This research discusses the accuracy of determining the height of the solar count by comparing the accuracy of the 2 methods. The method used is descriptive comparative based on field research with a qualitative approach. The technique of collecting data was done by means of observation, documentation and literature study. The purpose of this research is to test the accuracy of each calculation method, namely the calculation of the Sailing List (DIP) and the Sight Reduction Table (SRT). The results obtained in this study are the high calculation accuracy calculation method of calculating shipping science lists is more accurate with testing which is further discussed in this study.